Pengendalian Kualitas Produk Menggunakan Metode Six Sigma dengan Pendekatan DMAIC pada UD. Palapa - Desi Ginura Divarica Anjani; Edwin Agus Buniarto; Zaenul Muttaqien (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this research is to use the six sigma approach to assess the quality of cracker manufacturing at UD. Palapa in Nganjuk Regency. This technology was chosen because it allows for quantitative measurement and analysis of product defect levels, as well as the identification of defect-causing variables. The study was carried out using the DMAIC (Define, Measure, Analyze, Improve, Control) steps and statistical methods such as Pareto diagrams, fishbone diagrams, and C-chart control charts. According to the research, the cracker manufacturing process at UD. Palapa has an average sigma value of 2.74, which is still below the six sigma (6σ) threshold. This figure implies that the product fault rate remains fairly high. The most common forms of faults are irregular shape and uneven thickness, which are mostly produced by machine, human, process, and raw material problems. C-chart analysis reveals that most processes are still under control, while there are a few spots beyond the control boundaries that indicate unique variances. Based on these data, it is possible to infer that UD. Palapa's quality control system is still reactive and has to be improved in order to be more proactive. Routine equipment maintenance, operator training, the introduction of standard operating procedures (SOP), and more stringent raw material selection are all possible efforts. Six Sigma deployment has been shown to provide a full view of production quality conditions, as well as a foundation for future continuous improvement programs.